Comparing the sociology of culture in Bangladesh and India: Similarities and differences in Bangladeshi and Indian cultures - S M Nazmuz Sakib (SIMULACRA: JURNAL SOSIOLOGI, 2023)
The sociology of culture is an important field that examines how societies create, maintain, and transform their cultural practices and beliefs. In the context of Bangladesh and India, this field is particularly relevant due to their rich and diverse cultural heritage. This paper explores the sociology of culture in these countries, focusing on cultural similarities and differences. Through a literature review of research from anthropology, sociology, history, and related fields, we will examine the historical background of cultural development in both countries, considering the impact of colonialism, nationalism, globalization, language, ethnicity, and religion. We will then present a comparative analysis of cultural practices, beliefs, and values, drawing on empirical data and case studies. This paper aims to contribute to our understanding of the sociology of culture in Bangladesh and India by shedding light on their diverse cultural heritage and exploring the ways in which cultural practices and values are shaped by historical, social, and political factors. By comparing the cultural similarities and differences between these nations, we hope to deepen our understanding of how culture is influenced by the broader social and political context.